Occurrence of Oil Sardine (Sardinella longiceps) along Babubali Island in Gahirmatha Marine Wildlife Sanctuary, Odisha, India - Behera, Satyaranjan; Sivakumar, K.; Choudhury, B. C.; Sethy, Janmejay (Indian Forester, 2012)
No Abstarct